Synthesis, Spectral Studies and Theoretical Treatment of New Au (III) and Cu(II) Complexes of Bidenetate Ligands 2-Benzamido Benzothiazole, and 2-Actamido Benzothiazole. - Alias, Mahasin F; Seewan, Ameena N; Thamer, Hind F (Al-Nahrain Journal of Science, 2018)
New metal complexes of the ligands 2-Benzamido benzothiazole (B1), and 2-Acetamido benzothiazole (B2) with th metal ions Au (III) and Cu (II) were prepared in alcoholic medium. The prepared complexes were characterized by FT-IR, electronic spectroscopy, Magnetic susceptibility, Flame Atomic Absorption technique as well as elemental analysis and conductivity measurement. From the spectral studies, an square planar as a monomer structure proposed for Au (III) complexes and octahedral diameric structure for Cu (II) complexes. Semi-empirical methods (ZINDO/1, PM3 and ZINDO/S) were carried out to evaluate heat of formation ∆H˚f, binding energy ∆Eb, dipole moment for copper complexes .While AMBER method was used to calculate energies of Au (III) complexes. Also vibration frequencies, and electronic transitions of prepared ligands were calculated. The electrostatic potential HOMO and LUMO energies were calculated for the ligands to determine the reactive sites for these ligands.